P488 Putting the U.S. Army's rising rates of chlamydia and gonorrhea in perspective: a comparison with U.S. trends. (14th July 2019) - Jordan, Nikki; Gaydos, Joel; Garges, Eric
Abstract : Background: U.S. chlamydia and gonorrhea rates have increased for four consecutive years, reaching record highs in 2017. Similar trends were reported for the U.S. Army, with Army rates being elevated relative to the general population, due in part to demographic differences. A comparison of standardized rates was needed to put these differences in perspective. Methods: Incidence rates of chlamydia and gonorrhea reported during 2013–2017 among Army active members and U.S. citizens age 15–64 were standardized using the 2015 Army age and sex distribution. The CDC's National Electronic Disease Surveillance System and the Army's Disease Reporting System Internet were used for the analysis. Results: Crude and adjusted chlamydia rates (per 100, 000) were over 2-fold higher among Army members (adjusted 2017 rates: 2, 160 and 1, 005 in the Army and U.S, respectively). Army chlamydia rates were elevated for all age and sex strata. The Army's crude gonorrhea rates (per 100, 000) were elevated (annual rate range: 275–373 versus 156 to 266 in the U.S.); however, adjusted U.S. rates surpassed Army rates (2017 rates: 438 in the U.S. versus 360 in the Army). Elevations for chlamydia and gonorrhea were observed in Army women under 25 relative to U.S. women 15–24 (2017 crude rates: 11, 132 versus 3, 635, respectively, for chlamydia and 1, 117 vs 623, respectively, for gonorrhea). Crude gonorrhea rates were higher in U.S. men 25–44 relative to Army peers (2017 rates: 542 vs 269 for men 25–34, and 238 vs 106 for men 35–44, respectively). Conclusion: The Army's incidence of chlamydia was elevated relative to the general population even when demographic differences were taken into account. This may reflect higher individual or sexual network risks or better access to care. The Army's lower adjusted gonorrhea rates may reflect differences in high-risk sub groups such as MSM, differing sexual network risks, or unmeasured confounders. Disclosure: No significant relationships.